Experimental Evaluation of Bond Strength between Setting Retarder Added Concrete and Normal Concrete - Jin-Su Son; Chiwon Song; Won-Jong Chin; Young-Jin Kim; Jin-Young Lee (Advances in Civil Engineering)
The large size concrete structures are continuously placed with time delay due to practical reasons. The bond strength between old concrete and new concrete is related with a performance of concrete structures. In order to investigate bond strength of slant shear specimens, the specimens (100 × 100 × 300 mm) were fabricated and tested. Two fractions of setting retarder (0% and 1%), surface roughness (none, brushed, and chipping), and curing hours (8, 16, 24, and 72 hours) were considered as variables. Failure modes, compressive strength, and displacement were measured to evaluate the bond strength of specimens. As a result, chipping treatment, which is commonly applied to increase the bond strength between old and new concrete, did not show significant increase of bond strength. The addition of retarder shows that the increased bond strength compared with the chipping treatment. The addition of the retarder in concrete shows sufficient bond strength after the previous placing of 16 hours. Furthermore, the retarder-added specimens with additional brushing treatment of concrete surfaces showed increase of bond strength more than the specimens without brushing. From the test results, it is confirmed that the addition of the retarder can be a new method to increase the bond strength of the concrete surface in continuous placement of concrete.